An updated checklist of Araceae, Leguminosae and Myrtaceae of the department of Boyacá, Colombia, including keys to genera and new occurrence records - Lucas, Eve J.; Haigh, Anna L.; Castellanos, Cesar; Aguilar-Cano, José; Biggs, Nicola; Castellanos, Carolina C.; Fabriani, Federico; Frisby, Susan; García, Lina; Klitgård, Bente B.; Morales-Puentes, Maria Eugenia; Parra-O., Carlos; et al. (Phytotaxa, 2023)
Baseline checklists for the Leguminosae (Fabaceae), Araceae and Myrtaceae from the Colombian department of Boyacá are available from the Catalogue of Plants and Lichens of Colombia. These lists were supplemented by thorough herbarium and literature searches by a collaborative group of local and international experts, and further enhanced by local field collections. The result is authoritative taxonomic checklists for the three families including data regarding habit, plant uses and species conservation risk assessments for a subset of species. The checklists have notably increased the number of species reported from Boyacá and provide reliable, taxonomically up-to-date inventories for those families. Checklists are based on specimens vouchered in local herbaria and revised specimen metadata is lodged in the Colombian biological information platform CEIBA. The initiative demonstrates how relatively low levels of funding allow taxonomic experts working in networks to rapidly improve the taxonomic understanding of angiosperm species diversity in megadiverse countries like Colombia.